Distant motivation against short motivation - Mukhambetov, T.I. (BUKETOV BUSINESS REVIEW, 2021)
Object: This article examines the issues of comparative analysis of short, that is, near and long perspectives from the point of view of their impact on employee motivation. Another goal of the article is to develop practical recommendations for the development of Far Distant (Long-term) Motivation in the wage system. Methods: This study uses quantitative research methods and a trending data collection method. The data were collected through a survey using the same questionnaire in 1994 and in 2010, which made it possible to identify the dynamics of changes in employee motivation. The sample size was 250 respondents. Findings: The results show that long-term perspectives at work play a huge role for workers. Second, Far Distant Motivation is unfortunately underestimated by employers, as a result of which the potential for increasing employee productivity is not fully exploited. Conclusions: Research shows that Far Distant Motivation should become an essential element of the motivation system in a company focused on competitiveness. Its presence will increase the competitiveness of the company, the productivity of employees and achieve the integration of personnel into the strategic goals of the company. The widespread practice of Short-Term Motivation based on assessment and remuneration based on short-term results for certain categories of workers has significantly less motivational power than Far Distant Motivation based on assessment of merit and long-term performance results. Therefore, modern companies must build a combination of Short and Far Distant Motivation.